2019
DOI: 10.3390/e21030236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiative Electro-Magnetohydrodynamics Diminishing Internal Energy of Pressure-Driven Flow of Titanium Dioxide-Water Nanofluid due to Entropy Generation

Abstract: The internal average energy loss caused by entropy generation for steady mixed convective Poiseuille flow of a nanofluid, suspended with titanium dioxide (TiO2) particles in water, and passed through a wavy channel, was investigated. The models of thermal conductivity and viscosity of titanium dioxide of 21 nm size particles with a volume concentration of temperature ranging from 15 °C to 35 °C were utilized. The characteristics of the working fluid were dependent on electro-magnetohydrodynamics (EMHD) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…13 In a similar study, simulation of H 2 O-based nanofluid flow in a porous medium due to the Lorentz forces was studied by Sheikholeslami and Shehzad. 14 The impacts of slip flow and magnetic field along with a homogeneous-heterogeneous response on MHD Eyring-Powell fluid flow over a rotating disc have been investigated by Gholinia et al 15 Moreover, there are other valuable studies in the above-mentioned fields that are mentioned in References, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] for additional study.…”
Section: Introductionmentioning
confidence: 99%
“…13 In a similar study, simulation of H 2 O-based nanofluid flow in a porous medium due to the Lorentz forces was studied by Sheikholeslami and Shehzad. 14 The impacts of slip flow and magnetic field along with a homogeneous-heterogeneous response on MHD Eyring-Powell fluid flow over a rotating disc have been investigated by Gholinia et al 15 Moreover, there are other valuable studies in the above-mentioned fields that are mentioned in References, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] for additional study.…”
Section: Introductionmentioning
confidence: 99%
“…Following that, the application of this method was widespread. It was successfully used to solve many linear and nonlinear equations and problems, for example: simulation of nonlinear water waves (Tao, Song, & Chakrabarti, 2007), nonlinear heat transfer (Abbasbandy, 2006;2007;Rashidi et al, 2014;Sajid & Hayat, 2008),differential-difference equation (Wang, Zou, & Zhang, 2007), solving cubic and coupled nonlinear Schr€ odinger equations (Hassan & El-Tawil, 2011) and many others (Akram & Sadaf, 2017;Alamri, Ellahi, Shehzad, & Zeeshan, 2019;Ellahi, 2013;Khan, Bukhari, Marin, & Ellahi, 2019;Kumar & Kumar, 2014;Prakash, Tripathi, Triwari, Sait, & Ellahi, 2019;Riaz, Ellahi, Bhatti, & Marin, 2019;Zeeshan, Shehzad, Abbas, & Ellahi, 2019). These successful applications affirmed the authenticity, flexibility and effectiveness of HAM.…”
Section: Introductionmentioning
confidence: 90%
“…They managed to show that the shape factor causes stronger convection. Zeeshan et al [36] reported the effect of radiative nanofluid flow under a pressure gradient due to entropy generation and observed an increase in entropy with an increase in the pressure gradient. Ellahi et al [37] investigated flow of a power-law nanofluid with entropy generation and noted that the skin friction coefficient increases at the heated wall.…”
Section: Introductionmentioning
confidence: 99%